Complex Pythagorean neutrosophic normal interval-valued set with an aggregation operators using score values - Palanikumar, Murugan; Kausar, Nasreen; Deveci, Muhammet (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
The complex Pythagorean neutrosophic normal interval-valued set approach solves the multiple-attribute decision-making problem. We introduce the new concepts such as complex Pythagorean neutrosophic normal interval-valued weighted averaging, complex Pythagorean neutrosophic normal interval-valued weighted geometric, complex generalized Pythagorean neutrosophic normal interval-valued weighted averaging and complex generalized Pythagorean neutrosophic normal interval-valued weighted geometric operator. We demonstrate that complex Pythagorean neutrosophic normal interval-valued set satisfy algebraic structures such as associative, idempotent, bounded, commutative and monotonic properties. Additionally, we develop algorithm and flowchart that solve problems using these operators. Examples of using enhanced score values and accuracy values in real-world environments are provided in this paper. Artificial intelligence refers to the simulation or approximation of human intelligence in machines. Its goals include computer enhanced learning, reasoning and perception. Artificial intelligence is being used today across different industries, from finance to healthcare. Agricultural robots have been described as being highly dependent on computer and machine tool technology. Four factors can be used to evaluate the quality of a robotics system: the controller's sophistication, the software efficiency, the maximum moment of inertia, and the manufacturer's reliability. The best alternative can be determined by comparing expert opinions to the criteria. Therefore, the parameter V has a very significant impact on the results of the model. This comparison aims to prove that the models under consideration are valid and valuable by comparing them with the available and proposed models. In conclusion, the value of V significantly impacts the model performance. Based on the comparison and sensitivity analysis, we conclude that the proposed aggregation operation is superior and more reliable than the existing one. The criteria were compared to the most appropriate options based on expert assessments.
Keywords: Agriculture robots; Computer technology; Decision making; Aggregating operators; Complex Pythagorean neutrosophic set; DECISION-MAKING; FUZZY; TOPSIS; Automation & Control Systems; Computer Science; Engineering